2006
DOI: 10.1207/s15328015tlm1802_7
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENTS: Faculty, Students, and Actors as Standardized Patients: Expanding Opportunities for Performance Assessment

Abstract: Students and faculty benefited from their SP experience. A combination of SP types can provide a broad range of cost-effective preclinical learning experiences. Students, faculty, and actors as SPs each have specific strengths and weaknesses related to cost, training needs, feedback quality, and simulation fidelity. The goals of the encounter should guide the choice of SP type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 18 publications
1
34
0
4
Order By: Relevance
“…In our learning activities, instructors (independent of the simulated patient) evaluate clinical content, but Mavis et al reported that instructors gained insight into the abilities of their students by acting as patients. 14 Resources also influence the ability to use only community volunteers, including the time necessary to develop relationships with potential patient pools and the money needed if paid actors are necessary. The resources consumed by finding standardized patients who are either paid actors or actually have the conditions being portrayed could be prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…In our learning activities, instructors (independent of the simulated patient) evaluate clinical content, but Mavis et al reported that instructors gained insight into the abilities of their students by acting as patients. 14 Resources also influence the ability to use only community volunteers, including the time necessary to develop relationships with potential patient pools and the money needed if paid actors are necessary. The resources consumed by finding standardized patients who are either paid actors or actually have the conditions being portrayed could be prohibitive.…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review on peer-assessment in OSCEs found that using peer evaluators in an OSCE is appropriate in formative settings, promoting learning to all the students involved [9]. Though the literature on student SPs is less extensive, medical students have also been shown to be reliable and cost-effective SPs in formative OSCE settings [10]; furthermore, as with student examiners, Mavis and colleagues [11] reported that student SPs benefited from learning experiences gained during the OSCE encounter.…”
Section: Introductionmentioning
confidence: 99%
“…When neophyte students in psychiatric mental health nursing attempt to assume the mannerisms, personality, and problems of a client, they often present inaccurate portrayals (Browning, Collins, & Nelson, 2005). Other problems include students unconsciously helping each other with the communication process (Reams & Bashford, 2011), excessive self-disclosure, (Browning et al, 2005) and feelings of intimidation when faculty members play the role of the client (Mavis, Turner, & Lovell, 2006). For this HFPS activity, experienced faculty members would assume the role of the client out of the view of the students, offering an accurate, realistic, and less intimidating presentation.…”
Section: Designmentioning
confidence: 99%